2022
DOI: 10.7717/peerj.12794
|View full text |Cite
|
Sign up to set email alerts
|

Should I use fixed effects or random effects when I have fewer than five levels of a grouping factor in a mixed-effects model?

Abstract: As linear mixed-effects models (LMMs) have become a widespread tool in ecology, the need to guide the use of such tools is increasingly important. One common guideline is that one needs at least five levels of the grouping variable associated with a random effect. Having so few levels makes the estimation of the variance of random effects terms (such as ecological sites, individuals, or populations) difficult, but it need not muddy one’s ability to estimate fixed effects terms—which are often of primary intere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 42 publications
0
38
0
1
Order By: Relevance
“…We tested the likelihood ratio between models with the random effects structure of year nested within site vs. models with just site as a random effect. We found that models that included year within site differed significantly from models that included only site as a random effect, indicating that these models can parameterize temporal variation despite the grouping factor having only two levels (Gomes, 2022 ). This method accounts for the well‐documented phenomenon of interannual variation in insect pollinators (e.g., Herrera, 1988 ; Price et al, 2005 ).…”
Section: Analysis Methodsmentioning
confidence: 91%
“…We tested the likelihood ratio between models with the random effects structure of year nested within site vs. models with just site as a random effect. We found that models that included year within site differed significantly from models that included only site as a random effect, indicating that these models can parameterize temporal variation despite the grouping factor having only two levels (Gomes, 2022 ). This method accounts for the well‐documented phenomenon of interannual variation in insect pollinators (e.g., Herrera, 1988 ; Price et al, 2005 ).…”
Section: Analysis Methodsmentioning
confidence: 91%
“…Random effect models assist in controlling for unobserved heterogeneity when the heterogeneity is constant over time and not correlated with independent variables. If the random effects assumption holds, the random effects estimator is more efficient than the fixed effects model (Gomes, 2022). The results are as shown in Table 7 below.…”
Section: Random Effect Modelmentioning
confidence: 89%
“…Despite limiting models to just one random effect (i.e., whale ID) and reducing the number of random effects included in the model, singular fits persisted. Since this warning message may also relate to the variance of one or more combinations of the effects being close to zero 78 , we believe that the singular fit is due to the low sample size while splitting the data between many relevant fixed and random effects. Therefore, exclusion of relevant variables may not necessarily resolve the issue; thus, we selected models based on AIC, parsimony, and inclusion of variables relevant for explaining fGC variation (Table 1).…”
Section: Discussionmentioning
confidence: 99%